Barium Aspiration in an Infant: A Case Report and Review of Management - Jackson, M.; Kapur, N.; Goyal, V.; Choo, K.; Sarikwal, A.; Masters, I. B.; Isles, Alan F. (Frontiers in Pediatrics, 2014)
We describe a case of bilateral inhalation and alveolarisation of barium in an infant following a barium swallow for investigation of dusky spells associated with feeds. A bronchoscopy subsequently revealed the presence of a mid-tracheal tracheo-oesophageal cleft. We review the literature on barium aspiration, its consequences and make recommendations for management.